Speech Processing in Embedded Systems - Sinha, Priyabrata; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Speech Processing has rapidly emerged as one of the most widespread and well-understood application areas in the broader discipline of Digital Signal Processing. Besides the telecommunications applications that have hitherto been the largest users of speech processing algorithms, several non-traditional embedded processor applications are enhancing their functionality and user interfaces by utilizing various aspects of speech processing. Speech Processing in Embedded Systems describes several areas of speech processing, and the various algorithms and industry standards that address each of these areas. The topics covered include different types of Speech Compression, Echo Cancellation, Noise Suppression, Speech Recognition and Speech Synthesis. In addition this book explores various issues and considerations related to efficient implementation of these algorithms on real-time embedded systems, including the role played by processor CPU and peripheral functionality. This volume is perfect for engineers involved in the design and implementation of speech processing applications. .
Signal Processing Fundamentals -- Basic Speech Processing Concepts -- CPU Architectures for Speech Processing -- Peripherals for Speech Processing -- Speech Compression Overview -- Waveform Coders -- Voice Coders -- Noise and Echo Cancellation -- Speech Recognition -- Speech Synthesis -- Conclusion.
Keywords: Engineering; Logic design; Computer organization; Electronic circuits; Engineering; Signal, Image and Speech Processing; Circuits and Systems; Logic Design; Computer Systems Organization and Communication Networks; Electronic books